2012
DOI: 10.1007/s11746-012-2034-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Chemical Traits of Selected New Jojoba (Simmondsia chinensis (Link) Schneider) Genotypes

Abstract: Seeds from six selected jojoba genotypes were used in this study. Seed samples were analyzed for oil, protein, total carbohydrate, and simmondsin contents. The genetic relationships among jojoba genotypes were also determined. Highly significant differences among the genotypes were found for oil, protein, total carbohydrate and simmondsin contents. Genotype MD 8 recorded the highest oil content (54.95%), whereas genotype HD 6 had the lowest oil content (47.17%). However, the highest protein content (16.98%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…As a result, distinct genomic expressions were expected to be detected in the chemical parameters studied [ 35 ]. Al-Soqeer et al [ 36 ] concur that there are variances amongst jojoba plants. Our findings are consistent with those of Al-Soqeer et al [ 34 ], who assessed the development and yield of seven genotypes planted at Qassim University Farm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, distinct genomic expressions were expected to be detected in the chemical parameters studied [ 35 ]. Al-Soqeer et al [ 36 ] concur that there are variances amongst jojoba plants. Our findings are consistent with those of Al-Soqeer et al [ 34 ], who assessed the development and yield of seven genotypes planted at Qassim University Farm.…”
Section: Discussionmentioning
confidence: 99%
“…For plants that were roughly five years old, the seed yield per plant ranged from 335.3 to 821.6 g plant −1 . Through an evaluation of the oil seed percentage of jojoba shrubs, Al-Soqeer et al [ 36 ] found differences between genotypes which ranged between 47.17 and 54.95%. Eltaweel et al [ 37 ] recorded that vegetative and flowering chlorophyll a and b differed according to genotype, and the seed yield ranged between 1 and 3.5 kg shrub −1 and the oil percentage of seed ranged between 49.50 and 61.17% for eight years old plants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were published in this regard. Of these, few demonstrated variability in the content and quality of jojoba oil, and additional compounds, such as simmondsin (will be later elaborated) content among different jojoba genotypes (Benzioni et al 2005;Al-Soqeer et al 2012). In parallel, several methods for detecting genetic polymorphism and providing genotypes with molecular fingerprinting have been published and described in more detail in (Al-Obaidi et al 2017).…”
Section: Genetics and Diversitymentioning
confidence: 99%
“…Al-Obaidi et al [ 75 ] developed a set of RAPD-PCR-based biomarkers for both in vitro and in vivo jojoba cultivars. Al-Soqeer et al [ 76 ] observed highly significant differences among six jojoba genotypes in oil, protein, total carbohydrate and simmondsin contents. They compared the molecular data obtained from ISSR markers with the chemical traits obtained from the same genotypes.…”
Section: Genetic Diversity and Molecular Biology Approachesmentioning
confidence: 99%